Force sensing device design using a modified add-drop filter - Kulrod, K.; Sirawattananon, C.; Mitatha, S.; Srinuanjan, K.; Yupapin, P. P. (My University, 2012)
We propose a new sensing device using a modified add-drop filter known as a PANDA ring resonator type, in which the sensing unit is consisted of an optical add/drop filter and two nanoring resonators, where one ring is placed as a sensing device, the other ring is set as a reference. In operation, the external force is assumed to exert on the sensing ring resonator, which can form the measurement. The finite difference time domain (FDTD) method called Optiwave is used to manipulate the sensing behaviors of the proposed system. The obtained results have shown that the change in wavelength due to the change in sensing ring radii is seen, in which the wavelength shift of 1 nm resolution is achieved. The recovery and the reciprocal signals can also be formed, which can be used to approach to many advantages of measurements, including the possibility of standardizing measurement accuracy. The behavior of light within a PANDA ring resonator is also analyzed and reviewed. © 2010 Published by Elsevier Ltd.
Keywords: Force sensor; Optical sensor; Self calibration